Mapping crisis-era protectionism in the Asia Pacific region - Simon J. Evenett (Asian Development Bank Institute (ADBI), 2013)
This paper provides an account of the resort in recent years by governments in the Asia Pacific region to discrimination against foreign commercial interests. As in previous systemic economic crises, policymakers altered the mix of discriminatory policies employed. This time around governments of higher income economies in the region frequently softened the budget constraints of firms, offering a range of financial incentives that went beyond high-profile bank sector bailouts. Meanwhile, many developing countries in the Asia Pacific relied more on traditional forms of protectionism. The result is a more fragmented set of markets in the Asia Pacific region than before the crisis.
Keywords: F13; F53; 330; protectionism; asia-pacific region; wto; non-tariff measures; Protektionismus; Wirtschaftskrise; Asiatisch-pazifischer Raum